2017
DOI: 10.3382/ps/pex118
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive texture analyses of cooked patties made of chicken breast with the woody breast condition

Abstract: The woody breast (WB) condition negatively influences the texture characteristics and quality of intact broiler breast fillets (Pectoralis major). But the impact of WB on ground meat is unknown. The objective of this study was to evaluate the effects of WB on the texture and cook loss of ground meat made of broiler breast fillets. Broiler breasts (deboned 3 h postmortem) were collected on 3 separate trial d from the commercial deboning line and classified into normal and severe WB fillet categories. Individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 18 publications
7
25
1
Order By: Relevance
“…2018 ). However, there was no significant difference between normal and wooden breast patties in shear force ( Brambila et al., 2017 ). Therefore, corresponding processing types of products determined the textural property of meat products.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…2018 ). However, there was no significant difference between normal and wooden breast patties in shear force ( Brambila et al., 2017 ). Therefore, corresponding processing types of products determined the textural property of meat products.…”
Section: Discussionmentioning
confidence: 94%
“…In the aspect of intact breast meat, many researchers have demonstrated that raw wooden breast fillets exhibited poor WHC and bad hardness. As wooden breast myopathy worsened, chicken broiler breast exhibited poorer WHC, harder areas of raw meat, and different textural properties ( Brambila et al., 2017 , Dalgaard et al., 2018 ). This could be related to histological structure, which revealed that wooden breast presented muscle fiber fragmentation, myofibril swelling, hyalinization, macrophage infiltration, necrotic muscle fiber replacement with connective tissue, and interstitial connective tissue accumulation ( Soglia et al., 2016a , Soglia et al., 2016b , Dalle Zotte et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, some authors proposed meat processing solutions to minimize implications on product quality as summarized in Table . There are margins to mitigate undesirable effects on technological properties of processed products when abnormal meats are included in the formulation of grounded and finely comminuted meat products (Brambila et al., ; Brambila, Chatterjee, Bowker, & Zhuang, , Chen et al., ; Xing et al., ), however significant quality reduction can arise when high‐quality processed products (that is, enhanced whole‐muscle and ground products) are manufactured by using especially WB abnormal raw meat (Bowker, Maxwell, Zhuang, & Adhikari, ; Maxwell et al., ; Mudalal et al., ; Petracci et al., ; Soglia et al., ; Tijare et al., ). In addition, latest studies agree that overall manifestation of muscle abnormalities mainly affects the superficial section of pectoralis major muscle, while the deep section was less affected (Baldi et al., , ; Bowker & Zhuang, ; Bowker et al., ).…”
Section: Means Of Alleviation: Facts and Challengesmentioning
confidence: 99%
“…The instrumental texture of the cooked severe WB was harder than the normal breast fillets, and sensory analyses of the cooked WB showed more springiness and cohesiveness than the normal fillets ( Chatterjee et al., 2016 ). However, the sensory texture attributes of WB were not uniform throughout the entire Pectoralis major muscle ( Aguirre et al, 2018 ; Brambila et al, 2017 ). Tasoniero et al (2017) reported that the hardness of WB is related to the extra water trapped in the myofibrillar matrix (myowater).…”
Section: Wooden (Or Woody) Breast (Wb)mentioning
confidence: 99%